Early MRI for Pediatric Wrist Injuries—Prospective Case Series of 150 Cases - Courcey, Cynthia de; Jester, Andrea; Kaur, Sarbjit; Lindau, Tommy R.; Oestreich, Kerstin (Journal of Wrist Surgery, 2022)
Background Pediatric carpal injuries are a clinical challenge due to their non-specific clinical features and occult nature on plain radiography. We hypothesized that early magnetic resonance imaging (MRI) will allow prompt diagnosis and treatment stratification, and that distal pole fracture of the scaphoid requires a shorter duration of immobilization. This study aims to assess the injury pattern and clinical outcomes of under-16-year-olds treated with acute post-traumatic wrist injuries in accordance with the unit's protocol.Methods All patients under the age of 16 years treated for suspected pediatric wrist injuries in our tertiary pediatric hand and upper limb service were included. Prospectively collected data included patient demographics, radiological findings, treatment and adherence to the unit's protocol.Results There were 151 patients with a mean age of 12 years. The majority (72%) had occult bony injury with radiological evidence of fracture on MRI. The sensitivity and specificity of plain film radiography were 42.7% and 71.4%, respectively. Almost one in four patients benefitted from early MRI demonstrating no injuries, permitting early mobilization and discharge. The scaphoid was the most commonly injured carpal bone. Non-displaced fractures of the distal pole of the scaphoid in patients over 10 years old were treated with 4 weeks' immobilization with no adverse outcome.Conclusion Standardized care in our unit has yielded good results with low complication rate and fewer hospital appointments. Our results support the routine early use of MRI and a shorter duration of immobilization in fracture of the distal pole of the scaphoid at 4 weeks.Level of Evidence This is a level IV, case series study.
Keywords: carpus; scaphoid; fracture; pediatric; MRI